Penguatan Capacity Building pada Kelompok Perawatan Diri (KPD) Kusta Sumber Waras melalui Kegiatan Pemanfaatan Kompos dan Mikroorganisme Lokal (MOL) di Puskesmas Kecamatan Slahung Kabupaten Ponorogo - Alfu Laila; Use Etica; Lutfy Ditya Cahyanti (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Partners in this people empowerment program was KPD Leprosy Sumber Waras. Self Care Group (KPD) Sumber Waras is a group of leprosy patients or who have recovered from leprosy, which was initiated by Centre Public Healthy at Slahung District, Ponorogo city, East Java. The problems faced by partners were social and economic problems. The purpose of these people empowerment program was after this program the members of KPD skillfully to making compost and MOL (local microorganisms) independently. Futhermore, would improve the economy side of leprosy KPD members. Stages of activities undertaken in this program included pre- implementation stage that were 1) Socialization 2) Preparation tools and materials. The second stage was the implementation stage including: 1) Composting material 2) Material and practice of making the MOL. From this program, it could be concluded that 1) Partners have understood the material of composting and MOL 2) Partners have been able to make MOL 3) These people empowerment activities have been able to overcome the problems of partners.